Interpersonal violence and mental health outcomes following disaster. Issue 1 (January 2020) - Molyneaux, Robyn; Gibbs, Lisa; Bryant, Richard A.; Humphreys, Cathy; Hegarty, Kelsey; Kellett, Connie; Gallagher, H. Colin; Block, Karen; Harms, Louise; Richardson, John F.; Alkemade, Nathan; Forbes, David
Abstract : Background: Disasters pose a documented risk to mental health, with a range of peri- and post-disaster factors (both pre-existing and disaster-precipitated) linked to adverse outcomes. Among these, increasing empirical attention is being paid to the relation between disasters and violence. Aims: This study examined self-reported experiences of assault or violence victimisation among communities affected by high, medium, and low disaster severity following the 2009 bushfires in Victoria, Australia. The association between violence, mental health outcomes and alcohol misuse was also investigated. Method: Participants were 1016 adults from high-, medium- and low-affected communities, 3–4 years after an Australian bushfire disaster. Rates of reported violence were compared by areas of bushfire-affectedness. Logistic regression models were applied separately to men and women to assess the experience of violence in predicting general and fire-related post-traumatic stress disorder, depression and alcohol misuse. Results: Reports of experiencing violence were significantly higher among high bushfire-affected compared with low bushfire-affected regions. Analyses indicated the significant relationship between disaster-affectedness and violence was observed for women only, with rates of 1.0, 0 and 7.4% in low, medium and high bushfire-affected areas, respectively. Among women living in high bushfire-affected areas, negative change to income was associated with an increased likelihood of experiencing violence (odds ratio, 4.68). For women, post-disaster violence was associated with more severe post-traumatic stress disorder and depression symptoms. Conclusions: Women residing within high bushfire-affected communities experienced the highest levels of violence. These post-disaster experiences of violence are associated with post-disaster changes to income and with post-traumatic stress disorder and depression symptoms among women. These findings have critical implications for the assessment of, and interventions for, women experiencing or at risk of violence post-disaster.